Muscle fiber typology in national level football and its influence on in-game fatigue - Van de Casteele, F.; Lievens, E.; Van Vossel, K.; Hardeel, J.; Deprez, D.; Derave, W. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Physical game demands in football (soccer) are position-dependent and a large heterogeneity in muscle fiber typology exists among national level players (1). We could expect that it is advantageous for central midfielders, who cover a large total distance, to have a slow typology and for forwards, who sprint a lot, to have a fast typology. At the higher levels this could lead to a selection effect. Furthermore, it was shown that fast typology individuals (FT) fatigue more than slow typology individuals (ST) (2). Therefore, we investigated if muscle typology is different between national level football players who occupy other positions and secondly if FT experience more in-game fatigue than ST.